Genomics of Pattern Recognition Receptors Applications in Oncology and Cardiovascular Diseases - Kutikhin, Anton G.; Yuzhalin, Arseniy E.; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2013)
This book offers comprehensive information on the polymorphisms of genes encoding pattern recognition receptors (PRRs). Following a short description of the general role of PRRs in the immune system, the structure and function of Toll-like and NOD-like receptors are examined in detail. The main focus is on the role of inherited variation in PRRs and their correlation to cancer and cardiovascular diseases. A review of all epidemiological investigations is included, and a concept of genomic risk markers for the prevention of various diseases is also discussed.
The Biology of Toll-like Receptors and NOD-like Receptors: Toggles of Inflammation -- Pattern Recognition Receptors, Gene Polymorphisms, and Cancer: A Double-Edged Sword -- Structural Genomic Variation in Toll-Like Receptor 4 and Cancer -- Structural Genomic Variation in Other Toll-like Receptors and Cancer -- Structural Genomic Variation in Toll-Like Receptor Signaling Pathway and Cancer -- Structural Genomic Variation in Toll-like Receptor Pathway and Prostate Cancer -- Structural Genomic Variation in NOD-Like Receptors and Cancer -- Structural Genomic Variation in Pattern Recognition Receptors and Cardiovascular Diseases -- Hot Spots In the Field: Where Should We Go.
Keywords: Life sciences; Oncology; Human genetics; Immunology; Cardiology; Cell receptors; Life Sciences; Receptors; Immunology; Cancer Research; Human Genetics; Oncology; Cardiology